Prognostic model of the probability of successful extubation in the operating room after simultaneous kidney and pancreas transplantation - M. Sh. Khubutiya; M. V. Lebedev; N. K. Kuznetsova; A. M. Talyzin; A. G. Balkarov; N. S. Zhuravel; S. V. Zhuravel (Трансплантология (Москва))
Introduction. Early extubation at the end of surgery has a beneficial effect on the postoperative recovery of patients. Prolonged and highly traumatic surgery in recipients with severe initial pathology and tension(al) homeostasis doesn’t allow for safe procedure of early extubation in simultaneous kidney and pancreas transplantation (SKPT). This article aims at assessing the impact of recipient-related factors and intraoperative clinical factors on the possibility of successful extubation in the operating room after SKPT.Objective. To develop and substantiate a prognostic model for determining the probability of successful extubation in the operating room after SKPT depending on the impact of recipient-dependent factors and intraoperative clinical factors.Material and methods. A prospective single-center non-randomized study was conducted, enrolling 85 recipients who underwent SPKT in the N.V. Sklifosovsky Research Institute for Emergency Medicine in the period from 01.01.2008 to 31.11.2024. Among the recipients included in the study, there were 52 men (61%) and 33 women (39%); their median age was 35(31;39) full years. All patients were allocated in two groups. Group I included the patients who were successfully extubated at the end of surgery; group II included the patients non-extubated at the end of surgery who were transferred to the intensive care unit for prolonged mechanical ventilation. Using the binary logistic regression method, a prognostic model was developed for the probability of successful extubation of patients in the operating room after SKPT taking into account the presence of recipient-dependent factors and intraoperative clinical with their step-by-step exclusion according to Wald statistics.Results. The prognostic model of the possibility of successful extubation in the operating room was found statistically significant (p<0.001), with a sensitivity and specificity of 76.7% and 73.8%, respectively. Among recipient-dependent factors, an adjusted statistical significance was shown by body mass index (p=0.003) and the history of renal replacement therapy duration (p=0.037). Among intraoperative clinical factors, an adjusted statistical significance was shown by the epidural component of anesthesia (p<0.001), mean blood pressure >90 mmHg on reperfusion (p=0.048), the surgery duration factor (p=0.029), a total amount of fentanyl (p<0.001), and a total amount of cisatracurium (p=0.044).Conclusion. The prognostic model makes it possible to determine the tactics of intraoperative management of patients and optimize the strategy of anesthesiological support in order to ensure possible successful extubation of patients after the SKPT surgery.